2017
DOI: 10.17073/0368-0797-2017-4-329-335
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Model of Burning Process of Coal-Ore Pellets on Conveyor Machine

Abstract: Уральский федеральный университет имени первого Президента России Б.Н. Ельцина (620002, Россия, Екатеринбург, ул. Мира, 28) Аннотация. Выполнена разработка математических моделей процесса обжига рудоугольных окатышей на конвейерной машине. Структура рудо угольных окатышей представляет собой сферу, состоящую из равномерно распределенных гранул руды, известняка и топлива, радиусы которых задаются исходя из возможностей мельничного оборудования. Рассмотрены вопросы теплообмена между газом и материалом в поперечно… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The results of calculations of the change in temperature of a gas-air flow at the "layerbed" boundary along the length of CP showed that the blue chart is very close to the chart obtained by calculation given in [11] and does not differ significantly from the chart in [18]. Thus, we confirmed the adequacy of calculations experimentally.…”
Section: The Analysis Of the Characteristics Presented In Charts Insupporting
confidence: 87%
See 2 more Smart Citations
“…The results of calculations of the change in temperature of a gas-air flow at the "layerbed" boundary along the length of CP showed that the blue chart is very close to the chart obtained by calculation given in [11] and does not differ significantly from the chart in [18]. Thus, we confirmed the adequacy of calculations experimentally.…”
Section: The Analysis Of the Characteristics Presented In Charts Insupporting
confidence: 87%
“…5. Charts of comparisons of correctness of the calculations performed with similar calculations given in the scientific articles [11,18] and experimental data the temperatures of gas-air flows along the length of a calcination plant of OK-306 type. We accepted the following values of pressures of the gas-air flows generated the smoke exhausters from the calcination zone in the gas-air drying chamber: 620, 550 and 500 daPa.…”
Section: Discussion Of Results Of Studying the Process Of Redistributmentioning
confidence: 99%
See 1 more Smart Citation
“…Iterating in this procedure the optimal values of the parameters Tg 0i , Wgi at each stage of the decomposition provides the optimal sought-after sequence {Xi (Tg 0i , Wgi)} that optimizes the drying process of the multi-layer mass of pellets throughout the horizontal grate machine [21,22].…”
Section:  mentioning
confidence: 99%
“…The strengthening proceeds by pores reduction in the process of solid phase and liquid phase sintering. It is obvious that sintering should prevail, otherwise it will be impossible to obtain strong pellets [21][22][23].…”
mentioning
confidence: 99%